Futuro: Permanências e rupturas - Ribeiro, M. T.P. [UNESP]; Villela, V. M.J. [UNESP] (My University, 2000)
The authors look for solutions to our future. Among them we show the necessity of knowing the self and finding a religion seriously, as well as the integration of science and religion for the third millennium.
Future: Performance and rupture
Keywords: Faith language; Future; Religion; Science